The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.freeradbiomed.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The calcineurin antagonist RCAN1-4 is induced by exhaustive exercise in rat skeletal muscle

Abstract: The aim of this work was to study the regulation of the calcineurin antagonist regulator of calcineurin 1 (RCAN1) in rat skeletal muscles after exhaustive physical exercise, which is a physiological modulator of oxidative stress. Three skeletal muscles, namely extensor digitorum longus (EDL), gastrocnemius, and soleus, were investigated. Exhaustive exercise increased RCAN1-4 protein levels in EDL and gastrocnemius, but not in soleus. Protein oxidation as an index of oxidative stress was increased in EDL and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…We found that rat MCs have higher basal protein level of RCAN1.1 compared with RCAN1.4. HG induced the up-regulation of RCAN1.4 protein rather than RCAN1.1 protein, which is consistent with previous studies showed that RCAN1.1 is constitutively expressed in most issues, while RCAN1.4 transcription is induced de novo by several stimuli [32][33][34][35]. In addition, the mRNA level of RCAN1.4 rose in the early stage of HG stimulation and fell 12 h later, while the protein level of RCAN1.4 remained high at 36 h. The discrepancy between RCAN1.4 mRNA and protein levels suggested that there may be translational or post-translational regulation.…”
Section: Discussionsupporting
confidence: 92%
“…We found that rat MCs have higher basal protein level of RCAN1.1 compared with RCAN1.4. HG induced the up-regulation of RCAN1.4 protein rather than RCAN1.1 protein, which is consistent with previous studies showed that RCAN1.1 is constitutively expressed in most issues, while RCAN1.4 transcription is induced de novo by several stimuli [32][33][34][35]. In addition, the mRNA level of RCAN1.4 rose in the early stage of HG stimulation and fell 12 h later, while the protein level of RCAN1.4 remained high at 36 h. The discrepancy between RCAN1.4 mRNA and protein levels suggested that there may be translational or post-translational regulation.…”
Section: Discussionsupporting
confidence: 92%
“…RCAN1 is also overexpressed in the brains of individuals with Down syndrome, a disorder with an increased prevalence of AD . Neuronal expression of RCAN1 also increases with aging, and in response to traumatic stressors such as spinal cord injury and exhaustive exercise in muscle . The nutrient stress hyperglycaemia also induces RCAN1 expression in myotubes and pancreatic β‐cells .…”
Section: Rcan1 Expressionmentioning
confidence: 99%
“…19 Neuronal expression of RCAN1 also increases with aging, 20 and in response to traumatic stressors such as spinal cord injury 21 and exhaustive exercise in muscle. 22 The nutrient stress hyperglycaemia also induces RCAN1 expression in myotubes and pancreatic β-cells. 23,24 Such chronic increases in RCAN1 protein levels induce mitochondrial autophagy and a metabolic shift from oxidative phosphorylation to glycolysis in neuronal cells.…”
Section: The Acute Induction Of Rcan1 By Stress-associated Factors Suchmentioning
confidence: 99%
“…Oxidative muscle fibres mainly rely on sustained tonic contraction, and the intracellular Ca 2+ concentration is generally maintained at a relatively high level while glycolytic muscle fibres mainly undergo impulsive contraction with a Ca 2+ influx of transient and high intensity, which results in a higher concentration of Ca 2+ in slow muscle fibres than in fast muscle fibres (Zierath & Hawley, ). Recent studies have shown that the expressions of MyHC I and MyHC IIa are regulated by the Ca 2+ /calcineurin/NFAT pathway (Emrani et al, ; Ravel‐Chapuis, Bélanger, Côté, Michel, & Jasmin, ) pacifically, and increase of the intracellular Ca 2+ leads to calcineurin activation and NFAT dephosphorylation consequently. The dephosphorylated NFAT will translocate to the promoter of the gene involved in oxidative metabolism in the nucleus to promote the transformation of glycolytic muscle fibres to oxidative muscle fibres in skeletal muscle (Ehlers, Celona, & Black, ; Lomonosova, Turtikova, & Shenkman, ; Pfluger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…). Recent studies have shown that the expressions of MyHC I and MyHC IIa are regulated by the Ca 2+ /calcineurin/NFAT pathway(Emrani et al, 2015;Ravel-Chapuis, Bélanger, Côté, Michel, & Jasmin, 2017) pacifically, and increase of the intracellular Ca 2+ leads to calcineurin activation and NFAT dephosphorylation consequently. The dephosphorylated NFAT will…”
mentioning
confidence: 99%